Developing Tactics for Listening. More Listening. More Testing. More Effective - Richards J. C. Jack (New York, Oxford University Press, 2010)
More listening. More testing. More effective. NEW FOR THE THIRD EDITION. Four all-new, high-interest units. Tactics for Testing section presents test-taking skills and ractice tests for success on the TOEIC test and other exams. Downloadable audio files help students learn on the go. Conversation Corner in each unit provides. Pronunciation and Dictation practice. COMPONENTS. Student Book. Teacher's Book with Testing Program & Resource CD-ROM featuring:. Unit quizzes. Midterm and final tests in the style of the TOEIC* test and other exams. Vocabulary and Conversation Worksheets providing unit-preview and expansion activities. Class Audio CDs. Audio Download Center